Pengaruh Current Rasio, Total Assets Turnover, Debt Equity Ratio, dan Net Profit Margin Terhadap Pertumbuhan Laba: (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Anggun Dhewi Hapsari; Muhammad Jusman Syah (Pusat Riset dan Inovasi Nasional, 2024)
This study is to determine the influence of Current Ratio, Total Asset Turnover, Debt to Equity Ratio and Net Profit Margin on Profit Growth. This research was conducted on food and beverage companies listed on the Indonesia Stock Exchange for the period 2019 – 2023. The sample used in this study was 18 food and beverage companies. The sampling technique uses the purposive sampling method. This study uses a multiple linear regression analysis method, using the Statistical Package for the Social Science (SPSS) version 27. The results of this study show that the Debt to Equity Ratio has a significant positive effect on Profit Growth, while the Current Ratio, Total Assets Turnover and Net Profit Margin do not have a significant effect on Profit Growth.